2018
DOI: 10.1149/2.0351815jes
|View full text |Cite
|
Sign up to set email alerts
|

Co Nanoparticles Encapsulated in Porous N-Doped Carbon Nanofibers as an Efficient Electrocatalyst for Hydrogen Evolution Reaction

Abstract: One of the main challenges in commercializing electrolyzer is to develop cheap and highly active electrocatalysts toward hydrogen evolution reaction (HER). Although low Pt loadings in PEM electrolyzers have been demonstrated, it's still worthwhile to remove the Pt in the long term. Herein, porous N-doped carbon nanofibers containing encapsulated Co nanoparticles are in situ obtained by electrospinning and subsequent carbonization as efficient electrocatalysts for HER. The optimized catalyst treated at 800 • C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…In addition, Co species encapsulated within carbon materials have been developed for efficient HER. 103,[349][350][351][352] An ultra-thin N,B-codoped carbon cageencapsulated Co catalyst, named Co@BCN, was produced from the pyrolysis of ZIF-67 materials mixed with H 3 BO 3 . 352 ZIF-67 comprising Co metal nodes and organic linkers serves as the metal precursor and self-sacrificing template.…”
Section: Non-precious Metal Based Her Electrocatalystsmentioning
confidence: 99%
“…In addition, Co species encapsulated within carbon materials have been developed for efficient HER. 103,[349][350][351][352] An ultra-thin N,B-codoped carbon cageencapsulated Co catalyst, named Co@BCN, was produced from the pyrolysis of ZIF-67 materials mixed with H 3 BO 3 . 352 ZIF-67 comprising Co metal nodes and organic linkers serves as the metal precursor and self-sacrificing template.…”
Section: Non-precious Metal Based Her Electrocatalystsmentioning
confidence: 99%
“…The superior HER electrocatalysis performance resulted from more exposed active sites of graphitic edge plane rich carbon and high conductivity of carbon structure, whereas Co played a role to catalyze formation of carbon structure by graphitization. [ 74 ] Recently, Zhang et al [ 75 ] also synthesized porous N‐doped Co‐CNFs HER electrocatalyst via an electrospun method combined with a controlled carbonization process. The results showed that the carbonation temperature and the additive polyacrylonitrile (PAN) amount had a great influence on the morphology of electrocatalysts.…”
Section: Electrospun Nanocatalysts For Electrochemical Water Splittingmentioning
confidence: 99%
“…As discussed in the electronic modulation to improve HER performance, some of the electrocatalysts are CNFs‐based nanomaterials 83‐112 . It is well known that the electrospinning technique is a facile and versatile strategy to prepare functional electrocatalyst embedded in CNFs.…”
Section: Electrocatalytic Water Splitting Based On the Electrospun Namentioning
confidence: 99%